Using the "MyPlate Musical" to Increase Nutrition and Exercise Knowledge in Children. (14th February 2022) - Besnilian, Annette; Plunkett, Scott W.; Butleroff‐Leahy, Helen
Abstract : We evaluated the effectiveness of a school‐based, educational theater program (i.e., MyPlate Musical ) on nutrition/exercise knowledge of elementary student performers and viewers. Data were collected in four elementary schools with high percentages of Latinos and students eligible for free/reduced price meals. In Schools 1–3, pretest and posttest data were used from a total of 425 viewers and 220 performers. At School 4, 267 viewers and 75 performers served as their own control. Results indicated that student performers and student viewers of the theatrical performances had increased general nutrition/exercise knowledge and MyPlate knowledge from pretest to posttest and the effects were stronger in the treatment group than the control group. Educational theater appears to be a viable method to increase nutrition/exercise knowledge.